The influence of technological factors on foam-gaseous silicate formation mixtures and product properties/Technologinų veiksnių įtaka putų-dujų silikatbetonio formammo mišinų ir produkto savybėms - Laukaitis, Antanas (Journal of Civil Engineering and Management, 1998)
The aim of this work was to investigate 300 kg/m3 density foam-gaseous silicate concrete production parameters and properties. The optimal mentioned density product formation parameter determination was conducted in a wide density interval. The raw material chemical composition is given in Table 1. Sand slime and porous silicate concrete mixture formation was performed in a laboratory mixer at 750 RPM. Surface active agents sulphanol and OP-10 (ethylphenyl ethylene glycol ether) was used for this purpose. An additional blowing agent-aluminium powder hydrophilizated with sulfanol (20 g/kg) was used. Formation mixture plasticity strength was calculated according to Equation 1. Low-density porous silicate concrete sample compression strength depends not only on raw material fineness, binder amount, but also on its structure. Cast silicate concrete samples (without aluminium powder) were formed to determine the milled sand fineness needed for the optimal mixture activity. Their compression strength at 1100 kg/m3 density was calculated using equation 2. The sample compression strength dependency on mixture activity and sand fineness is given in Fig 1. The cast silicate concrete mixture technological parameters are given in Table 2. The mixtures activity is 20%, when the sand fineness approaches 130 m2/kg and 27% – 340, 31% – 500. Surface active materials amount (0,1 – 0,2%) lowers the silicate concrete samples compression strength insignificantly (Fig 2). The formation mixture envolves the surrounding air during sand slime and surface active agent mixing and partly swells. The amount of entrained air depends on the mixing time (Fig 3). However the main result is reached in 5 min. The slime density decreases from 1.7 to 0.8 kg/1, ie by 2.1 times. The mixing of surface active materials with all the mixture components is more effective, then whipping the slime separately with surface active agent and then adding lime and mixing again with the blown sand slime (Fig 4). This is explained by the fact, that when lime is added to the blown sand slime, its structure is partly destroyed. The surface active additives lower the foam silicate concrete formation mixture fluidity (Fig 5), due to the absorbed air during mixing. Sulphanol is a more effective surface active agent, than OP – 10 (Fig 5). It is impossible to reach a sample density lower than 400 kg/m3, when surface active agents are mixed with silicate concrete mixture. That is why experiments were conducted where aluminium powder was added, ie a foam-gaseous silicate concrete was produced. Its density depends an V/S ratio and aluminium powder amount (Fig 6). The investigation of 300 kg/m3 density porous silicate concrete mass plasticity strength showed that it is the highest for gaseous silicate concrete and the lowest for foam silicate concrete. Foam-gaseous silicate concrete mass plasticity strength occupies an intermediate position (Fig 7). The porous silicate concrete mixtures highest temperature also depends on the porous silicate type. A gaseous silicate concrete mixture reaches 88 °C already in 30 min. Foam silicate concrete temperature increases more slowly and reaches 60 °C in 60 min. Foam-gaseous silicate concrete mixture temperature occupies an intermediate position and reaches 69 °C after 36 min (Fig 8). The sample compression strength is the highest for foam silicate concrete and the lowest for gaseous silicate concrete. Foam-gaseous silicate concrete sample compression strength occupies an intermediate position and depends directly on pores produced by whipping sand slime with surface active materials and mixture mixing with Al powder, ratio (Fig 9). This is predetermined by the different pore origin and pore structure formed during different degrees of mass warm-up. The latter was discussed in our earlier publications [8,13,15]. Article in Lithuanian. First Published Online: 26 Jul 2012